Places of memory and place attachment: A study at the neighborhood scale in Istanbul - Erkan, Eda; Sungur, Asli; Turkyilmaz, Cigdem Canbay (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2024)
Places of memory are often locations where individuals connect with their own life stories. In this respect, places of memory can strengthen people's attachment to place. However, due to various reasons, some places of memory are lost as a result of rapid and wide-ranging transformations in the city, leading to interruptions in the continuity of memory. Beginning with the question, Do rapid and wide-ranging changes in the city affect individuals' places of memory and place attachment?, this study examines the changes experienced in Istanbul through existing and lost places of memory at the neighborhood scale.Three field studies were conducted in the Kuzguncuk Neighborhood, K & uuml;& ccedil;& uuml;kyal & imath; District, and Postane Neighborhood, located on the Anatolian side of Istanbul, each with distinct physical and demographic structures related to the sea. A total of 150 respondents, fifty from each area, answered survey questions. Data were analyzed using the SPSS program. The effects of changes triggered by land fill in coastal areas of Istanbul over time have also been observed in the residents' places of memory. The most mentioned places of memory include coastal and sea-related areas, parks and gardens, religious buildings, shopping buildings, educational buildings, transportation buildings, cafes and restaurants, cultural buildings, and accommodation buildings. Significant relationships emerged between place attachment values and variables such as duration of residence, educational status, and employment status, varying across different areas. However, no significant relationship was found between place attachment values and age or gender across the three areas. Among the three areas, the conservation zone of Kuzguncuk experienced the least change and showed the highest place attachment values.
Keywords: Memory; place attachment; places of memory; Architecture